Computer Ability Anxiety, Self-Efficacy Beliefs in Statistical Studies, Student Attitudes towards Course Statistics: An Empirical Study of Undergraduate Students in the Mathematics Study Program - Sessu, Andi; Arofah, Irvana; Ningsi, Besse Arnawisuda (IJBLE Scientific Publications Community Inc., 2025)
In the 21st century, the learning process continues to develop and undergo a paradigm shift. One of the characteristics of the 21st century is the presence of aspects of information, computing, automation, and communication that influence the learning paradigm. In learning statistics, it is not only cognitive skills that support student learning success but also non-cognitive skills. This study aims to determine the effect of student computer ability anxiety and self-efficacy beliefs on student attitudes toward statistical courses. The sample of this study was 203 students of the Mathematics Study Program of Pamulang University who were selected using a simple random sampling technique. Data collection techniques in this study used instruments with a Likert scale. The effect on the research variables was analyzed using structural equation modeling to determine the effect. From the results of the analysis, it is obtained that there is a direct influence of computer ability anxiety on self-efficacy beliefs in learning statistics, there is a direct influence of computer ability anxiety on attitudes towards statistics courses, there is a direct influence of self-efficacy beliefs in learning statistics on attitudes towards statistics courses, and there is an influence of computer ability anxiety in learning statistics on attitudes towards statistics courses through self-efficacy beliefs.